Physiological Traits and Rainfed Rice Grain Yield Treated with Cow Manure and Plant Growth Promoting Rhizobacteria Consortium - Purwanto; Rahayuani Ratnaningsih Hanim; Na’imatul Bayyinah Lafi; Naila Khusna Syarifah Risqa; Anik Leana Ni Wayan; Sarjito Agus; Supartoto; Mudmainah Siti; Yousif Ramzy A.; Ahmed Mohamed Omer Omer; Hanifa Hana (BIO Web of Conferences)
Agricultural intensification in the long term has had the impact of decreasing soil organic matter levels so that rice production tends to stagnate. The return of organic matter and the application of rhizobacteria is an action in the effort to the reclamation of paddy soil to be productive again. This research was conducted to examine the effect of the dosage of organic manure combined with the application of the PGPR consortium on the agronomic, physiological traits, and yield of aromatic rice plants to achieve sustainable rice production. The experiment was carried out using a Randomized Block Design 3 x 3 factorial and provide with replication. The first factor was the selected PGPR consortium application (P0 = control: P1+ PGPR consortium isolate R08 + R11, and P2 = PGPR consortium isolate R08 + Rhizobium sp. LM-5) and the second factor was cow manure application (0, 15 and 30tons ha-1). Application of organic fertilizer and the PGPR consortium was able to increase vegetative growth, nutrient uptake (N, P, and K), as well as the physiological character of rice plants. The interaction between the dose of organic fertilizer and the PGPR consortium affects the net assimilation rate, crop growth rate, and yield of rice plants. The highest yield was achieved at a dose of organic fertilizer of 30 tons ha-1 and the PGPR consortium isolate R08+Rhizobium sp. LM-5 of 11.68 tons ha-1.